Desistance from Sexual Offending or Not Reoffending?: a Taxonomy of Contact Sex Offenders - Cooley, Brooke N. (Criminology, criminal justice, law & society, 2022)
This paper explored why contact sex offenders lack reoffending, and a taxonomy was developed to better understand the desistance process, or more commonly, the non-reoffending process. Through qualitative conversational interviews with 29 contact sex offenders, it was found that contact sex offenders can be categorized into two broad groups. First, the criminal career sex offender who had persistent habitual offending. This category was comprised of a relatively small number of the sample (20.7%). This category can then be further broken down into two smaller categories, the desisters and the non-reoffenders. The desisters lacked reoffending due to cognitive transformations, while non-reoffenders were able to manage their sexual deviant behaviors due to strategies such as therapy, religious practices, and avoidance. Only two participants could be considered desisters, while the other participants were non-reoffenders. This is a noteworthy finding, demonstrating how rare it is to desist from contact sex offending based on scholars’ definitions of desistance as a process. Conversely, contact sex offenders who are not habitual persistent offenders lack reoffending because they never came to see themselves as "sex offenders" nor do they feel they have problems to address as their crimes were temporary and situational. This group contained the majority of the sample (79.3%) and was further divided into taxonomic subgroups. This study established the need to differentiate between career criminal sex offenders and those who are situational and temporary. Persistent offenders and situational offenders need different treatment practices, and they have different non-reoffending pathways.